The Challenges of Developing Tourism Events in Bromo Tengger Semeru National Park - Rosyidi, Muhammad Iqbal (Journal of Indonesian Tourism and Development Studies, 2018)
Tourism in Bromo Tengger Semeru National Park has been considered important for national earning and local community development. As a conservation area, the development of tourism in Bromo Tengger Semeru should consider conservation principles. The purpose of this research is to identify the challenges of developing tourism events in TNBTS especially dealing with sustainable development. The research method used is qualitative method with descriptive analysis technique. In-depth interviews were conducted to explore the perceptions of the government, organizer, and community regarding the conduct of tourism event in TNBTS. The literature study was conducted to provide more complete data and information. Furthermore, researcher conduct field observations twice, the first observation was during the Yadnya Kasada event and the second one was on normal days. This research has successfully identified three challenges of tourism event development in TNBTS namely the institutional, event sustainability, and rivalry with competitors.Keywords: event tourism, national park, sustainable development.